Immer diese Mütter Eine Untersuchung der Mutterfigur in gegenwartsliterarischen Beispielen unter Einbezug figurentheoretischer Überlegungen, historischer Entwicklungen und sozio-kultureller Einflüsse - Eva-Maria, Obermann (Wissenschaftliche Buchgesellschaft (wbg), 2023)
Always these mothers. These protective and nurturing, self-sacrificing beings who give life yet seem deadly and dangerous at the same time. The ambivalence of the mother imagination runs through both the symbolic charge and the historical development of the figure. In addition to the figure-theoretical derivation, this work includes a historical outline and a socio-cultural inventory before turning to the analysis of various mother figures in contemporary German-language literature. From the mother as a pathological figure who has a negative effect on the child, to the mother as a void and the child's associated identity crisis, to the mother as the main character who experiences her own crisis through motherhood, various contemporary literary works are considered, analyzed and compared. Digressions on how-to literature and entertaining literary mother figures complete the consideration of literary mothers.